(3fXQjI Gdfehs - (3QhHQJ(B, (3Uhdhs ((3HjQhJ(B:s (3eQcR OQGSGJ GdhMOI GdYQHjI(B,s, 2000)
(3JLO aj gPG GdcJGH (B: (3NUGFU GdChVGY GdeJhGJQI , eYGed QCS GdeGd , fehPL ef Ohf EMdGd eHGTQ , fehPL HfhYjf ef GdCUhd GdQCS eGdjI , GdSjGSI GdEbJUGOjI aj fehPL ddfeh eXGgQ GdSjGSI GdEbJUGOjI , QCS GdeGd GdHTQj, GdJcfhdhLjG GdOGNdjI , GdSdYI GdESJgdGcjI GdLOjOI CacGQ TheHjJQjI , OQhS hEbJQGMGJ Mhd fXQjI Gdfeh Gdcdjs
Keywords: (3GdJfejI GdGbJUGOjIs